Association Between the Rate of Treatment Response and Short-Term Outcomes in Childhood Guillain-Barré Syndrome - Jin, Mei; Zhao, Libo; Liu, Jing; Geng, Weijin; Zhao, Ziwei; Li, Chunzhen; Xue, Jingru; Sun, Suzhen (Frontiers in Neurology, 2021)
Introduction: Few studies have examined the association between the rate of treatment response and the outcome of pediatric Guillain-Barré syndrome (GBS). Therefore, our study aimed to identify treatment response in relation to the short-term outcomes of GBS. Further, we investigated its potential predictive value for prognosis. Methods: Our retrospective study included children diagnosed with GBS in the Pediatric Neurology Department of the Children's Hospital of Hebei Province from 2016 to 2020. According to the rate of response from the standard intravenous immunoglobulin (IVIg) treatment, patients were divided into two groups: rapid-response GBS (initial response within 7 days) and slow-response (initial response within 8–30 days). The GBS disability score (Hughes Functional Grading Scale) was used to assess the children's functional disability at nadir, 1 month, and 6 months after onset. Results: Among the 36 children included in the study, 18 (50%) and 18 (50%) were rapid and slow responders, respectively. Time from IVIg treatment to the initial response was significantly shorter in the rapid-response group (5 [3–6.25] days vs. 10.5[8.75–15] days in slow-response GBS, p < 0.001). Hughes score at 1 month was worse than the rapid responders (Fisher's exact test, p = 0.006). Survival analysis (Kaplan–Meier) with respect to regaining the ability to walk independently (Hughes Functional Grading Scale of 2) within 1 month after onset was significantly different among the two groups (log-rank test for trend, p = 0.024). The abnormal levels of cerebral spinal fluid proteins and autonomic dysfunction were more frequent in the slow-response group than those in the rapid group (p < 0.05). Conclusion: The rate of response to IVIg treatment was correlated with short-term outcomes in children with GBS and had predictive value for prognosis. The role of patient's initial responses to treatment could be significantly valuable in developing more effective and efficient treatment options.